Community Development in the Rural Areas through Traditional Indigenous Knowledge - Godfrey, Barigye; Siraje, Kaaya (International Journal of Research in Sociology and Anthropology, 2019)
The desire to change the community is buttressed in its sustainability and equitability through imperative and rationale of community governance and knowledge-ability. The rural setting is characterized by the agrarian setting: peasants, pastoralists, fishermen, hunters and gatherers. These people depend on land practices for sustenance through agriculture (crop and animals). Also, the rural area is seen as the place where the elderly, disabled, victims of war, unemployed, drug addicts and those with poor political governance reside. Such vulnerability reflects lack of buffers against contingencies to social conventions, disasters, physical incapacity, unproductivity and exploitation; low living people/ the marginalized. The paradigm shift in practice of activities for community change in the rural setting entails appraisal, analysis, planning, experimenting, implementing, monitoring and evaluation that leads to sustainable development through and use of traditional indigenous knowledge. Community mobilization brings together people to pursue common interests by creating a sense of unity, ownership and self–control. The process gets people to overcome their differences, to begin dialogue on an equal basis and to determine issues that affect their community, enabling communities especially the poor and other marginalized groups to participate, negotiate, demand, change and hold accountable institutions that affect their livelihoods and well-being, ease access to community- driven development. Increased indigenous technologies, approaches and methods in the rural areas improve peoples’ visual representation of their knowledge, judgment and preference. They tend to increase commitment and enthusiasm to generate consensus. This progressive change is synonymous with sustainable development designed to improve the economic and social means that the total stock of environment (resources) be put into use in socio-economic and other related aspects to satisfy human needs.